Miniproteins as phage display-scaffolds for clinical applications - Zoller, Frederic; Haberkorn, Uwe; Mier, Walter (Molecules, 2011)
Miniproteins are currently developed as alternative, non-immunoglobin proteins for the generation of novel binding motifs. Miniproteins are rigid scaffolds that are stabilised by alpha-helices, beta-sheets and disulfide-constrained secondary structural elements. They are tolerant to multiple amino acid substitutions, which allow for the integration of a randomised affinity function into the stably folded framework. These properties classify miniprotein scaffolds as promising tools for lead structure generation using phage display technologies. Owing to their high enzymatic resistance and structural stability, miniproteins are ideal templates to display binding epitopes for medical applications in vivo. This review summarises the characteristics and the engineering of miniproteins as a novel class of scaffolds to generate of alternative binding agents using phage display screening. Moreover, recent developments for therapeutic and especially diagnostic applications of miniproteins are reviewed.
Gesehen am 23.01.2023